Regulatory variant in FZD6 gene contributes to nonsyndromic cleft lip and palate in an African‐American family. Issue 5 (7th May 2015) - Cvjetkovic, Nevena; Maili, Lorena; Weymouth, Katelyn S.; Hashmi, S. Shahrukh; Mulliken, John B.; Topczewski, Jacek; Letra, Ariadne; Yuan, Qiuping; Blanton, Susan H.; Swindell, Eric C.; Hecht, Jacqueline T.
Abstract: Nonsyndromic cleft lip with or without cleft palate (NSCLP) is a common birth defect affecting 135, 000 newborns worldwide each year. While a multifactorial etiology has been suggested as the cause, despite decades of research, the genetic underpinnings of NSCLP remain largely unexplained. In our previous genome‐wide linkage study of a large NSCLP African‐American family, we identified a candidate locus at 8q21.3‐24.12 (LOD = 2.98). This region contained four genes, Frizzled‐6 ( FZD6 ), Matrilin‐2 ( MATN2 ), Odd‐skipped related 2 ( OSR2 ) and Solute Carrier Family 25, Member 32 ( SLC25A32 ). FZD6 was located under the maximum linkage peak. In this study, we sequenced the coding and noncoding regions of these genes in two affected family members, and identified a rare variant in intron 1 of FZD6 (rs138557689; c.‐153 + 432A>C). The variant C allele segregated with NSCLP in this family, through affected and unaffected individuals, and was found in one other NSCLP African‐American family. Functional assays showed that this allele creates an allele‐specific protein‐binding site and decreases promoter activity. We also observed that loss and gain of fzd6 in zebrafish contributes to craniofacial anomalies. FZD6 regulates the WNT signaling pathway, which is involved in craniofacial development, including midfacial formation and upper labial fusion. We hypothesize, therefore, that alteration in FZD6 expression contributes to NSCLP in this family by perturbing the WNT signaling pathway. Abstract : We identified a promoter variant in Frizzled 6 (FZD6) that segregated with nonsyndromic cleft lip and palate in a large African‐American family. This variant creates a novel protein‐binding site that decreases promoter expression and causes craniofacial anomalies in zebrafish. These results demonstrate that variation in FZD6 vt causes a functional change which may contribute to nonsyndromic cleft lip and palate in this family.